Pengaruh Profitabilitas, Tingkat Utang, Intensitas Aset Tetap dan Ukuran Perusahaan Terhadap Manajemen Pajak - Erlitasari, Tyas; Pahala, Indra; Utaminingtyas, Tri Hesti (LPPM Universitas Negeri Jakarta, 2022)
This study aims to determine the effect of profitability, level of debt, intensity of fixed assets and firm size on tax management. Indicators in measuring tax management use the effective tax rate (ETR). The research data uses secondary data in the form of financial statements for LQ45 companies during 2016 to 2020 with a total of 65 observations from 13 companies. Based on the research results obtained: Profitability, Intensity of Fixed Assets and Firm Size have an effect on tax management. While the level of debt has no effect on tax management. Based on the adjusted r-square value of 0.9875, it means that 98.75% of the tax management variables are influenced by the four independent variables in this study. While the remaining 1.25% is influenced by other variables not included in this study. Therefore, further research can add other independent variables such as inventory asset intensity, capital intensity and tax facilities to increase the adjusted r-square value and not limit only LQ45 companies and can add research years to more than 5 years. Keywords: Company Size, Debt Level, Fixed Asset Intensity, Profitability, Tax Management.